Life Management for Busy Women: Living Out God's Plan with Passion and Purpose - George, Elizabeth (Thomas Nelson, Inc., 1979)
This unique book will strike a chord with women hungering to live orderly lives that are a testimony to their faith.
Keywords: Christian life; Non-Fiction; Religion